On the Ischnosoma fauna of Georgia (Coleoptera: Staphylinidae: Tachyporinae) - Assing, Volker; Schülke, Michael (Contributions to Entomology = Beiträge zur Entomologie, 2017)
Three species of the Ischnosoma spelaeum group are described and illustrated, all of them most likely with very restricted distributions: Ischnosoma acutum spec. nov. (Georgia: Svaneti, Racha); I. barbigerum spec. nov. (Georgia: Svaneti); I. molle spec. nov. (Georgia: Adjara). Type material of I. major (Luze, 1901) and I. caucasicum Kocian, 1997 is revised. Additional records of previously described species of Ischnosoma Stephens, 1829 are reported from Georgia, partly also from other regions. Seven species of the genus have reliably been recorded from Georgia, two species of the I. pictum group and widespread, five of the I. spelaeum group and with restricted distributions. The presence of an additional species of the I. spelaeum group, I. caucasicum, requires confirmation. The distributions of the species of the I. spelaeum group are revised and mapped. Several previous literature records are zoogeographically implausible and consequently probably erroneous. Nomenclatural Acts • Ischnosoma acutum spec. nov. – urn:lsid:zoobank.org:act:62214E44-BF50-4608-95B5-BDDA2B0936FC • Ischnosoma barbigerum spec. nov. – urn:lsid:zoobank.org:act:314DE8C9-E254-4171-A502-F710E896BCFD • Ischnosoma molle spec. nov. – urn:lsid:zoobank.org:act:75E5A095-ACCC-4862-877D-76464BA33ABE